Evaluation of a biomethane, food and biofertiliser polygeneration system in a circular economy system. (December 2022) - Bose, A.; O'Shea, R.; Lin, R.; Long, A.; Rajendran, K.; Wall, D.; De, S.; Murphy, J.D.
Abstract: Biomethane is a viable alternative to natural gas and diesel for decarbonising hard-to-abate sectors such as agriculture, industry and heavy transport. Unlike conventional biogas upgrading, photosynthetic biogas upgrading cogenerates biomethane, biofertiliser and microalgal bioproducts with the potential to improve resource utilisation and process performance in a circular economy. In this paper, a photosynthetic biogas upgrading-based polygeneration process is proposed and analysed to co-produce biofuel (biomethane), bio-fertiliser (digestate) and food ( Spirulina powder, protein supplement) using agricultural feedstock. Based on a multi-criteria performance assessment, the economic and environmental benefits of the process are demonstrated. Thermodynamic performance of the process revealed that reducing the energy for greenhouse heating to cultivate microalgae would enable a higher energy output than input. Using economic allocation, a carbon footprint of biomethane less than 10 gCO2-eq /MJ (lower than 32.9 gCO2-eq /MJ for sustainable biomethane use in transport in the EU Renewable Energy Directive (Recast) (RED-II)); Spirulina protein of 0.8 kgCO2-eq /100 g protein (compared to 50 kgCO2-eq /100 g protein for beef); and digestate of 0.4 kgCO2-eq /kgN (comparing positively to 1.5–3 kgCO2-eq /kgN for synthetic nitrogenous fertiliser) was achieved. Unlike the current RED-II mandated methodology, the analysis established that the energy, CO2 emissions, land and water footprints of each co-product are best represented using an economic allocation principle. Based on the extended nutrition profile, Spirulina as a complete food outperforms most meat and plant-based protein alternatives in terms of CO2 emissions, land, and water footprints. Graphical abstract: Image 1 Highlights: Grid-quality biomethane (<2.5 %v CO2, <1%v O2 ) emissions were below 10 gCO2-eq /MJ. Carbon footprint of Spirulina powder as food was 0.8 kgCO2-eq /100 g protein. The carbon footprint of digestate as a fertiliser was 0.4 kgCO2-eq /kgN. Sustainability of co-products is best represented using economic allocation.